Accession of Part of Eastern Galicia to Romania in 1919: Military and Political Aspects - Stepan Borchuk; Andrii Korolko; Alexander Reient (Codrul Cosminului, 2020)
The article deals with the military and political aspects of the accession of part of Eastern Galicia to Romania in 1919. The diplomatic and military plans of Romania, Poland, and the Entente for the capture of south-eastern Galicia are described; the course of the offensive Operation Pokutia led by the Romanian troops at the end of May 1919 shows the causes of the defeat of the Ukrainian armed forces; the peculiarities of the establishment of Romanian power in the region are revealed, and the uneasy relations between the Romanian and Polish military administrations concerning the seized lands were traced in June – August 1919.